LPS-induced senescence of macrophages aggravates calcification and senescence of vascular smooth muscle cells via IFITM3 - Ya-Ping Fang; Xin Yang; Ying Zhang; Xiao-Dong Zhu; Xiao-Xu Wang; Yan Liu; Wen Shi; Jia-Yi Huang; Yu Zhao; Xiao-Liang Zhang (Renal Failure)
Background Cellular senescence, macrophages infiltration, and vascular smooth muscle cells (VSMCs) osteogenic transdifferentiation participate in the pathophysiology of vascular calcification in chronic kidney disease (CKD). Senescent macrophages are involved in the regulation of inflammation in pathological diseases. In addition, senescent cells spread senescence to neighboring cells via Interferon-induced transmembrane protein3 (IFITM3). However, the role of senescent macrophages and IFITM3 in VSMCs calcification remains unexplored.Aims To explore the hypothesis that senescent macrophages contribute to the calcification and senescence of VSMCs via IFITM3.Methods Here, the macrophage senescence model was established using Lipopolysaccharides (LPS). The VSMCs were subjected to supernatants from macrophages (MCFS) or LPS-induced macrophages (LPS-MCFS) in the presence or absence of calcifying media (CM). Senescence-associated β-galactosidase (SA-β-gal), Alizarin red (AR), immunofluorescent staining, and western blot were used to identify cell senescence and calcification.Results The expression of IFITM3 was significantly increased in LPS-induced macrophages and the supernatants. The VSMCs transdifferentiated into osteogenic phenotype, expressing higher osteogenic differentiation markers (RUNX2) and lower VSMCs constructive makers (SM22α) when cultured with senescent macrophages supernatants. Also, senescence markers (p16 and p21) in VSMCs were significantly increased by senescent macrophages supernatants treated. However, IFITM3 knockdown inhibited this process.Conclusions Our study showed that LPS-induced senescence of macrophages accelerated the calcification of VSMCs via IFITM3. These data provide a new perspective linking VC and aging, which may provide clues for diagnosing and treating accelerated vascular aging in patients with CKD.